Attachment to stress ulcer prophylaxis guideline in the neurology wards of two teaching and non-teaching hospitals: A retrospective survey in Iran - Farzaneh Foroughinia; Mohammad Madhooshi (Wolters Kluwer Medknow Publications, 2016)
Objective: In this study, we aimed to evaluate the attachment to stress ulcer prophylaxis (SUP) guideline in the neurology wards of two teaching and nonteaching hospitals. Methods: A total of 243 patients were retrospectively reviewed in the neurology wards of two teaching and nonteaching hospitals. To assess the appropriate administration of SUP, an internal guideline was prepared using the American Society of Health-System Pharmacists (ASHP) protocol. Findings: SUP prescriptions were noncompliant with ASHP guideline in about 93.1% and 84.6% of cases in the nonteaching and teaching hospitals, respectively. Conclusion: SUP may be better practiced in teaching hospitals versus nonteaching ones.